Proteomics Reveal the Inhibitory Mechanism of Levodopa Against Esophageal Squamous Cell Carcinoma - Li, Zhenzhen; Li, Xin; He, Xinyu; Jia, Xuechao; Zhang, Xiaofan; Lu, Bingbing; Zhao, Jimin; Lu, Jing; Chen, Lexia; Dong, Ziming; Liu, Kangdong; Dong, Zigang (Frontiers in Pharmacology, 2020)
High recurrence rates and poor survival of patients with esophageal squamous cell carcinoma (ESCC) after treatment make ongoing research on chemoprevention drugs for ESCC particularly important. In this study, we screened a large number of FDA-approved drugs and found levodopa, a drug used to treat Parkinson’s disease, had an inhibitory effect on the growth of ESCC cells. To elucidate the molecular mechanisms involved, we applied quantitative proteomics to investigate the anti-tumor activity of levodopa on ESCC. The results suggest that levodopa could down-regulate oxidative phosphorylation, non-alcoholic fatty liver disease, and Parkinson’s disease pathways. Major mitochondrial respiratory compounds were involved in the pathways, including succinate dehydrogenase subunit D, NADH-ubiquinone oxidoreductase Fe-S protein 4, and mitochondrial cytochrome c oxidase subunit 3. Down-regulation of these proteins was associated with mitochondrial dysfunction. Western blotting and immunofluorescence results confirmed the proteomics findings. Cell viability assays indicated mitochondrial activity was suppressed after levodopa treatment. Reduced mitochondrial membrane potential was detected using JC-1 staining and TMRE assays. Transmission electron microscopy revealed changes in the morphology of mitochondria. Taken together, these results indicate that levodopa inhibited the growth of ESCC through restraining mitochondria function.